Exploring Students Potential and Creativity Through Science Exploration with Water Rockets and a Stunning Interactive Approach - Nailinnajah, Nailinnajah; Septiana, Masnal Khamal; Triwardani, Melinda; Luthfi, Nur Fadilla Aulia (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
A water rocket is an educational game that requires propulsion in the form of air and water pressure. In water rockets, the air of a room will press in all directions and water flows towards lower pressure. The purpose of this research is to analyze the effect of different elevation angles and water volume on the farthest distance of parabolic motion of water rockets. This research uses an experimental study method conducted by 2nd semester students of PSDKU PGSD Kebumen. Data collection techniques using practicum and documentation. Data analysis techniques were carried out with water rocket experiments 3 times. The experimental results showed that: 1) To produce the farthest distance traveled, the water rocket uses an elevation angle of 60 ° with a fixed water volume of 400 ml. 2) The farthest distance using a volume of 600 ml with a fixed elevation angle of 45°. The results of this study can be used as student materials for science exploration and interactive approaches so as to explore the potential and creativity of students.